An Improved Peridynamic Model with Energy-Based Micromodulus Correction Method for Fracture in Particle Reinforced Composites (Communications in Computational Physics, 2022)
We introduce an improved bond-based peridynamic (BPD) model for simulating brittle fracture in particle reinforced composites based on a micromodulus correction approach. In the peridynamic (PD) constitutive model of particle reinforcedcomposites, three kinds of interactive bond forces are considered, and precise definition of mechanical properties for PD bonds is essential for the fracture analysis inparticle reinforced composites. A new micromodulus model of PD bonds for particle reinforced composites is proposed based on the equivalence between the elasticstrain energy density of classical continuum mechanics and peridynamic model andthe harmonic average approach. The damage of particle reinforced composites is defined locally at the level of pairwise bond, and the critical stretch criterion is describedas a function of fracture energy based on the composite failure theory. The algorithmprocedure for the improved BPD model based on the finite element/discontinuousGalerkin finite element method is brought forward in detail. Several numerical examples are performed to test the feasibility and effectiveness of the proposed model andalgorithm in analysis of elastic deformation, crack nucleation and propagation in particle reinforced composites. Additionally, the impact of distribution, shape and sizeof particles on the fractures of composite materials are also investigated. Numericalresults demonstrate that the improved BPD model can effectively be used to analyzethe fracture in particle reinforced composites.
Keywords: Particle reinforced composite; peridynamics bonds; micromodulus correction; fracture; crack growth path.